THE ROLE OF BRAND AWARENESS IN MEDIATING THE EFFECT OF ELECTRONIC WORD OF MOUTH ON PURCHASE DECISION(A Case Study of The Originote Products in Gianyar Regency) - Dewa Agung Ayu Winda Amritaswari; I Gst. Ngurah Jaya Agung Widagda K (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
One of the rapidly growing industries is the personal care and beauty sector, with various facial care brands emerging with different innovations and benefits to attract consumer interest and intention to use their products. Due to the high public interest in self-care and beauty, competition among skincare brands has become increasingly intense. One of the beauty brands in Indonesia that is currently gaining popularity among consumers from various segments is The Originote. In early 2024, The Originote experienced a decline in sales, indicating a decrease in customers’ repurchase intention and low public brand awareness of The Originote, which in turn affects purchase decisions. Purchase decision is a process in which consumers begin by recognizing a problem and proceed to making a final decision to purchase a product. This study aims to analyze the role of brand awareness and electronic word of mouth on purchase decision. The sample consisted of 30 users of The Originote products who had purchased the product at least once within a month. The research was conducted in Gianyar Regency. The method used was a survey with a questionnaire technique, analyzed using descriptive and inferential statistics. The results show that Electronic Word of Mouth has a positive and significant effect on Purchase Decision, but does not have a significant effect on Brand Awareness. Meanwhile, Brand Awareness has a positive and significant effect on Purchase Decision, but cannot mediate the effect of Electronic Word of Mouth on Purchase Decision. These findings are expected to serve as a reference for future research and provide practical implications, suggesting that The Originote should expand its marketing reach to increase broader brand recognition.